Modernità e ortodossia: strategie di conciliazione e dissidenza nell'insegnamento della filosofia nei collegi gesuitici del primo Settecento - Anna Rita Capoccia (Les Dossiers du GRIHL)
Anna Rita Capoccia's contribution is based on the analysis of manuscripts created by Giulio Gori and other Jesuit professors at Roman College in the first twenty years of eighteenth century.There are here described professors' "hidden" opposition to official precepts by the Order about teaching and an introduction strategy to Atomist and Cartesian modern philosophy; these strategies unhinged doctrinal tasks that were the theoretical structure of Jesuit Order's orthodoxy.